ANALYTICAL STUDY OF THE STRENGTH CHARACTERISTICS OF COMPACTED SOIL (GEOMATE Journal, 2023)
In recent years, many cases of river embankments and levees collapsing due to sudden torrential rains and earthquakes have been reported. The mechanism of compaction and collapse based on the mechanics of unsaturated soil is important to establish a quality evaluation method for embankment structures in consideration of performance design. Therefore, in this study, compaction behavior considering soil materials was analyzed using the soil-water-air coupled finite element analysis program (DACSAR-MP). The obtained compacted specimens of silt-mixed sand were then subjected to flooding analysis and constant volume shear analysis to determine the strength properties from the numerical analysis. The results of the analysis showed that over compaction was confirmed by considering air dissolution, and that suction stress had a significant effect on shear strength, resulting in a significant reduction in strength on the wet side. In conclusion, the analysis showed that construction on the dry side is safer and stronger in construction using D values.